Antecedents of Muslim Students’ Adoption of Mobile Banking: An Extended TAM and UTAUT Approach - Heri Sudarsono; Lak lak Nazhat El Hasanah; Jannahar Saddam Ash Shidiqie; Indri Supriani (Jurnal Organisasi dan Manajemen, 2024)
Purpose – This study aims to determine the factors that affect the intention of Muslim students to adopt mobile banking (m-banking) services at Islamic banks. Methodology – This study included a sample of 336 Muslim students employed by Islamic banks as respondents. The model incorporates 11 constructs: perceived risk (PR), perceived trust (PT), habit (HA), compatibility (CO), perceived usefulness (PU), perceived ease of use (PEU), effort expectancy (EE), performance expectancy (PE), facilitating conditions (FC), social influence (SI), and intention to adopt m-banking (IN). It is a combination of the unified theory of acceptance and use of technology (UTAUT) and the technology acceptance model (TAM). Findings – Muslim students’ intention to adopt mobile banking was positively influenced by perceived usefulness, performance expectancy, and facilitating conditions. Nevertheless, the intention of Muslim students to adopt mobile banking remains unaffected by factors such as perceived ease of use, effort expectancy, or social influence. Perceived ease of use and perceived trust affect perceived usefulness, while perceived risk, perceived risk, habit, and compatibility affect perceived ease of use. Originality – This study employs the TAM-UTAUT model, which consists of 11 components, to determine the intention of Muslim students towards using mobile banking.